Peran Keterlibatan Mahasiswa dalam Fundraising Zakat Terhadap Peningkatan Kesejahteraan Mahasiswa Penerima Manfaat - Inayatul Widad Nasution1; Yenni Samri Juliati Nasution (Jurnal Sains dan Teknologi, 2023)
Student involvement in zakat fundraising activities has a crucial role in improving the welfare of student beneficiaries. Social solidarity realized through student participation not only creates a caring campus environment, but also has a positive impact on increasing zakat funds. The aim of research regarding the role of student involvement in zakat fundraising in improving the welfare of student beneficiaries is to determine the impact and contribution resulting from student participation in zakat fund collection activities. This research method is qualitative. And it was found that student involvement in zakat fundraising not only stimulates fund growth, but also forms an inclusive and empathetic campus community, supporting the vision of improving student welfare.